The European Union relationships with Ukraine through the prism of the Chernobyl accident. - Korienieva, Anna (2023)
The primary objective of this thesis is to provide empirical evidence supporting the hypothesis that the European Union (EU) securitized the Chernobyl accident and to investigate the implications of this securitization on the relationship between the EU and Ukraine. The thesis employs a comprehensive theoretical framework for examining securitization, integrating insights from the Copenhagen and the Paris Schools’ approaches. The robust analysis relies on context and practices description in conjunction with content and discourse analysis of the primary documents such as statements, press releases and communications issued by the key EU bodies. Both qualitative and quantitative analyses point only to limited securitization dynamics. Furthermore, it concludes that Chernobyl played an important role in the initial phase of the relations between the EU and Ukraine. After the EU’s enlargement, the Chernobyl factor started to diminish. Overall, this thesis contributes to a better understanding of the interconnectedness between securitization discourse and international relations dynamics, providing insights into the multifaceted implications of the Chernobyl narrative in the EU.